SIMULASI GERAK OSILASI PAKSA DENGAN REDAMAN MENGGUNAKAN SPREADSHEET EXCEL DAN MACRO VISUAL BASIC FOR APPLICATION - Rosliana Eso (Universitas Halu Oleo, 2017)
This paper discus about the forced oscillation with damping which it is simulated by using Excel Spreadsheet and Macro Visual Basic For Application. The system was considerating as a string with mass m where it oscillates on the influence of force and damp. The Equations of forced oscillation with damping processes in spreadsheet excel and simulates using Macro Visual Basic For Application approached. To verify the accuracy we use the numerical solution of Heun and Runge-Kutta Merson methods, the two-order differential equations are converted to first order linear differential equations and then look for algorithms for each numerical method. Algorithm of numerical method of input, process and output. This paper also shows that Runge-Kutta Merson numerical method has higher accuracy than Heun numerical method in solving the equation of forced oscillation with damping.Keywords: Numerical Solutions, Excel Spreadsheet, Visual Basic For Application